Celiac disease and ulcerative colitis as comorbid diseases – the diagnostic challenge - Graczyk, Julia; Makowska, Oliwia; Łężyk-Ciemniak, Eliza; Szaflarska-Popławska, Anna; Krogulska, Aneta (Pediatria Polska - Polish Journal of Paediatrics, 2022)
This study reports the case of a 17-year-old girl with a medical history of abdominal pains, diarrhoea, nausea, vomiting, weight loss, and stools with mucus and blood. The patient was diagnosed with celiac disease (CeD) and ulcerative colitis. No improvement was observed after a gluten-free diet, metronidazole, mesalazine, and systemic steroid treatment. The patient was administered azathioprine, and the systemic steroid therapy was repeated. The clinical condition worsened, and so Infliximab induction treatment was initiated; however, it was discontinued due to lack of response. Cyclosporine treatment was provided with good results. This case is particularly significant because, although the co-occurrence of CeD and inflammatory bowel disease in children is rare, bearing in mind the possible relationship between these disease entities in the diagnosis and treatment of children with gastrointestinal complaints may improve clinical practice and prevent the incorrect diagnosis or worsening the patient’s clinical condition and delaying the implementation of appropriate treatment.